Role of the microbiota in oncogenesis - Z. V. Grigorievskaya; I. N. Petukhova; N. S. Bagirova; V. V. Aginova; P. V. Kononets (Сибирский онкологический журнал)
Objective. To conduct a systematic analysis of data on the results of studies published in scientific journals on the pro-carcinogenic and anticarcinogenic role of microbiota, as well as on the therapeutic potential of microorganisms in oncogenesis.Material and Methods. The articles were searched using the Web of Science, Scopus, PubMed, Medline, and eLIBRARY databases. More than 150 sources dedicated to the study of the carcinogenic function of the microbiota and the possible influence of its species and quantitative composition on the efficacy and toxicity of antitumor therapy were found. Data from 71 articles were included in the review.Results. The relationship between the gut microbiota and cancer is multifactorial and bilateral: pro-carcinogenic on the one hand and anti-carcinogenic on the other hand. Microorganisms can induce tumor growth and cancer development through DNA damage and induction of mutagenesis, trigger oncogenic signals, disruption of barrier function, as well as immune response system disruption. Depletion of microbiota, the development of dysbiosis and induction of chronic inflammatory state are negative factors in the development of cancer. The anticancer effect of microorganisms is presumably based on the production of tumor-suppressive metabolites that function through multiple immune reactions. Maintenance of barrier function, competitive exclusion of pathogenic bacteria, and direct action on immune cells to prevent inflammation are also important protective factors. The presence of intratumor microorganisms in various tumors has been noted. Changes in species and quantitative composition of cancer patients’ microbiota are influenced by diet, taking antibacterial drugs, chemo-, immuno- and radiation therapy. In turn, the microbiota can affect the ongoing treatment. Numerous studies on the influence of the gut microbiota on the efficacy of immunotherapy, particularly in disseminated melanoma, have been conducted. It has been suggested that primary resistance to immunotherapy may be related to the abnormal composition of the gut microbiota. The level of gut microfora composition diversity and the number of Faecalibacterium or Bacteroidales in the fecal microbiota have been suggested to be the predictor of response to anti-PD-1 therapy. To change the composition and activity of the gut microbiota, several therapeutic methods, such as the administration of prebiotics, probiotics, synbiotics, postbiotics, fecal microbiota transplantation, as well as the change in the microbiota composition through a specific diet, are available.